2013
DOI: 10.4137/ccrpm.s12882
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate Detects Baseline Reductions in Chloride and Increases in Response to Albuterol in Cystic Fibrosis Patients

Abstract: Impaired ion regulation and dehydration is the primary pathophysiology in cystic fibrosis (CF) lung disease. A potential application of exhaled breath condensate (EBC) collection is to assess airway surface liquid ionic composition at baseline and in response to pharmacological therapy in CF. Our aims were to determine if EBC could detect differences in ion regulation between CF and healthy and measure the effect of the albuterol on EBC ions in these populations. Baseline EBC Cl−, DLCO and SpO2 were lower in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…Future investigations need to use exhaled breath condensate in ventilated patients with SARS-CoV-2-induced acute respiratory distress syndrome (ARDS) for measurement of chloride levels corrected by putting into ratio to a reference molecule or ion as outlined previously ( 14 ) and comparing patients with and without pulmonary edema in coronavirus disease. A reduction of chloride levels would confirm the hypothesis of a reduced CFTR function as was demonstrated in patients with cystic fibrosis ( 16 ).…”
supporting
confidence: 71%
“…Future investigations need to use exhaled breath condensate in ventilated patients with SARS-CoV-2-induced acute respiratory distress syndrome (ARDS) for measurement of chloride levels corrected by putting into ratio to a reference molecule or ion as outlined previously ( 14 ) and comparing patients with and without pulmonary edema in coronavirus disease. A reduction of chloride levels would confirm the hypothesis of a reduced CFTR function as was demonstrated in patients with cystic fibrosis ( 16 ).…”
supporting
confidence: 71%
“…Our initial research looking at the variability of EBC ions demonstrated that within subjects across three measurements on the same day the coefficient of variation is 30% for EBC Na + 54 . Review of the variability in response to the variability of EBC Cl − in response to saline where the coefficient of variation within subjects across baseline, 30, 60 and 90-minutes post nebulized saline was 46% 26 . Our results demonstrate changes from baseline exceed this inherent within subject variability suggesting that our results are not by chance or measurement error, but what is still unclear is if the level of change we observed is clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaled breath condensate samples were collected using the Jaeger EcoScreen as previously described 26 . To collect EBC while subjects were cycling, plastic tubing was used to connect the inlet port of the EcoScreen to the exhalation port of a Y-valve connected to the backside of the switching valve with the pneumotach attached to on the front side (setup pictured in supplemental material Figure 8 A & B).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of cardiac output was performed in triplicate at rest and duplicate during exercise at matched 25 W and anaerobic threshold (AT) with the subjects in an upright seated position on the cycle ergometer using a rebreathing technique described previously [ 15 18 ]. Briefly, using a 5-L anesthesia bag containing 0.7% acetylene, 9% helium, and 35% O 2 at a respiratory rate of 32 breaths/minute at the end of a normal expiration, the subjects were switched into the rebreathe bag and completed 6–10 consecutive breaths out of the bag.…”
Section: Methodsmentioning
confidence: 99%